The collision between the Yili and Tarim blocks of the Southwestern Altaids: Geochemical and age constraints of a leucogranite dike crosscutting the HP-LT metamorphic belt in the Chinese Tianshan Orogen. - Gao, Jun; Klemd, Reiner; Qian, Qing; Zhang, Xi; Li, Jilei; Jiang, Tuo; Yang, Yongqiang (Tectonophysics, 2011)
A ca. 600m-long, 0.5-20m-wide NW-SE trending granite dike crosscuts the high pressure-low temperature (HP-LT) Tianshan metamorphic belt, the foliation of which is parallel to the main ENE regional trend in the Chinese South Tianshan Orogen. It is mainly composed of plagioclase, K-feldspar, quartz, muscovite, biotite and secondary chlorite, while fluorite, zircon and xenotime occur as accessories. The immediate country rock is a quartz-biotite-plagioclase schist, which grades several tens of meters away from the granite dike into a chlorite-mica-albite schist. The latter schist is intimately intercalated with blueschist layers and boudins. The A/CNK value of the granite dike samples varies from 1.15 to 1.27 indicating a strongly peraluminous composition. CaO/Na2O ranges from 0.06 to 0.17 and Al2O3/TiO2 from 240 to 525, similar to the ratios of strongly peraluminous (SP) granites exposed in 'high-pressure' collision zones such as the Himalayas. A zircon U-Pb age of 285Ma was obtained for the granite dike, thus constraining the upper limit for the age of HP-LT metamorphism. The petrological and geochemical data suggest that the SP leucogranite dike intruded during the exhumation of overthickened crust in the post-collisional setting between the Yili (-Central Tianshan) and Tarim blocks. The dataset presented here in conjunction with previously published data corroborate that the HP-LT metamorphism must have occurred earlier than the Permian in the Tianshan Orogen. Therefore, the collision between the Yili (-Central Tianshan) and Tarim blocks and the final amalgamation of the Southwestern Altaids must have been terminated in Late Paleozoic and not in Triassic times as previously suggested. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dgeo.IGM.c3geoc.thecol
Keywords: Collision; Leucogranite dike; Southwestern Altaids; Tarim block; Tianshan; Yili block